Meningkatkan Motivasi Siswa dalam Pembelajaran IPAS dengan Berbantuan Media Diorama pada Siswa Kelas V SDN Karangrejo 02 - Charisma Dianti; Titin Masfingatin (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Motivation to learn is certainly one of the important things in determining the success of learning. However, students often feel a loss of motivation to learn so that students experience a decrease in learning motivation which will affect student learning outcomes. Therefore, it is important for teachers to create strategies to increase students' learning motivation. Strategies that can be implemented by teachers include using interactive learning media and can increase students' active participation during learning. The aim of this research is to determine students' learning motivation after implementing science learning using diorama learning media. This research uses descriptive qualitative methodology, examining the process and influence of implementing diorama media on student learning motivation. The data collected for this research took the form of direct observation, student interviews and analysis of several documents used to collect data, which was then analyzed using descriptive analysis methods, the form of this research is Classroom Action Research (PTK). The results obtained from this research are that the application of the Diorama of the Nature of Light learning media in science and science learning in class V at SDN Karangrejo 2 succeeded in increasing student motivation in learning. Students who were previously passive and did not play much of a role in the learning process after implementing learning using the Nature of Light Diorama showed significant changes in their activity in learning.